Collecting weather data in the field with high spatial and temporal resolution using iButtons - Mittra S; Etten, Jacob van; Franco T (Bioversity International, 2013)
This technical guideline explains how to collect temperature and humidity data using the Data logger iButtons reference DS-1923 Hygrochron. This device measures temperature and/or humidity and records the result in a memory section.